2013
DOI: 10.1021/bm400928b
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-caprolactone) Nanofibers with a Self-Induced Nanohybrid Shish-Kebab Structure Mimicking Collagen Fibrils

Abstract: A three-dimensional structure consisting of poly(ε-caprolactone) (PCL) nanofibers covered by periodically spaced PCL crystal lamellae, a self-induced nanohybrid shish-kebab (SINSK) structure, was created using electrospinning followed by a self-induced crystallization. The resulting structure that resembles the nanotopography of natural collagen nanofibrils in the extracellular matrix (ECM) of human tissues could serve as a tissue engineering scaffold. The formation mechanism of the self-induced shish-kebab st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 49 publications
3
62
0
Order By: Relevance
“…The first approach, controlled polymer crystallization on electrospun fibers either by incubation in polymer solution or by polymer solvent evaporation, creates lamellae on fibers with e.g. shish-kebab structures on fiber surfaces 57 . Alternatively, solvent extraction 810 , salt leaching 11 or calcination of electrospun fibers made up of two components yields porous surfaces by selective removal of the sacrificial component 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The first approach, controlled polymer crystallization on electrospun fibers either by incubation in polymer solution or by polymer solvent evaporation, creates lamellae on fibers with e.g. shish-kebab structures on fiber surfaces 57 . Alternatively, solvent extraction 810 , salt leaching 11 or calcination of electrospun fibers made up of two components yields porous surfaces by selective removal of the sacrificial component 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of interest to study the influence of this surface modification on cell growth and attachment to the NFSK surface. Studies in literature have proven that PCL nanofiber mats and NFSKs can support cell growth . Wang et al recently showed that cells were able to survive when seeded directly onto PCL NFSK scaffolds .…”
Section: Cytocompatibility Of Nfsksmentioning
confidence: 99%
“…50 Wang et al recently showed that cells were able to survive when seeded directly onto PCL NFSK scaffolds. 50 In the current work, in addition to unadorned PCL nanofibers, unmineralized NFSKs and NFSKs after 2 and 5 days of mineralization were evaluated for cytotoxicity. A live/dead assay was used to examine the cytocompatibility of cells attached to the nanofiber mat surface.…”
Section: Cytocompatibility Of Nfsksmentioning
confidence: 99%
“…A strategy that is currently being explored is to control for the mineral organization including spatial distribution and orientation during the mineralization process, which can be achieved using a template called nanofiber shish kebabs (NFSK) . NFSK are formed via polymer crystallization of electrospun nanofibers as shown in Figure . Our group has previously described this method to mimic mineralized collagen fibrils of bone .…”
Section: Introductionmentioning
confidence: 99%